Faktor-Faktor yang Mempengaruhi Jumlah Tenaga Kerja Terserap pada Sub Sektor Industri Makanan Skala Sedang dan Besar di Kalimantan Selatan - Aulia Safira Putri; Siregar, Syahrituah (PPJP ULM, 2025)
This study aims to determine the simultaneous, partial effects, and dominant factors influencing the amount of absorbed labor in the medium and large scale of food industry sub sector in South Kalimantan. It employs a quantitative approach using secondary data from the Central Statistics Agency of South Kalimantan Province with multiple linear regression analysis method on time series data from 2008 to 2020. The results indicate that simultaneously, all three independent variables have a significant effect on the amount of absorbed labor. Partially, wage levels and fuel and electricity costs have a negative and significant effect, while output value has a positive but not significant effect. The wage level variable is the most dominant factor influencing the amount of absorbed labor in the medium and large scale of food industry sub sector in South Kalimantan.